2019
DOI: 10.21511/im.15(1).2019.06
|View full text |Cite
|
Sign up to set email alerts
|

The internet and e-commerce diffusion in European countries (modeling at the example of Austria, Poland and Ukraine)

Abstract: This article analyzes the influence of Internet and e-commerce diffusion in the development of European countries. Conclusions about the faster spread of Internet technologies in the modern world, especially in developing countries, due to the achievement of so-called “saturation points” by developed countries of the world (e-commerce markets in Ukraine and Poland are at the stage of formation and active growth) have been made. The purpose of this article is to construct an economic and mathematical toolkit fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 20 publications
(11 reference statements)
0
7
0
Order By: Relevance
“…Digital infrastructure is the main influencing factors on digital economy and trade, from our study and existing research. Zatonatska et al ( 2019 ) conducted research on the development of the Internet and e-commerce in European countries, such as Austria, Poland, and Ukraine, and showed that the spread of Internet technology has a significant impact on the development of e-commerce. At the same time, Internet technology and broadband Internet access have spread faster in low-income countries owing to the late diffusion of digital technologies.…”
Section: Discussionmentioning
confidence: 99%
“…Digital infrastructure is the main influencing factors on digital economy and trade, from our study and existing research. Zatonatska et al ( 2019 ) conducted research on the development of the Internet and e-commerce in European countries, such as Austria, Poland, and Ukraine, and showed that the spread of Internet technology has a significant impact on the development of e-commerce. At the same time, Internet technology and broadband Internet access have spread faster in low-income countries owing to the late diffusion of digital technologies.…”
Section: Discussionmentioning
confidence: 99%
“…In the article (Rosario et al, 2021) it is proved that marketing approaches, such as IoT, big data, artificial intelligence, and machine learning, allow tracking in real time the relationship between business efficiency and advertising. Many studies focus on the importance of big data in the e-commerce and e-business industry (Riddle, 2020;Ryfiak, 2020;Zatonatska et al, 2019;Zatonatska et al, 2021;Mykhalchuk et al, 2021) or cryptocurrency market development (Suslenko et al, 2022;Zatonatska et al, 2022). Such research is extremely relevant for forecasting and making optimal management decisions in times of uncertainty and risk.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This also contributed to the result. Households traditionally walk to grocery stores (Zatonatska, et al, 2019)…”
Section: Case Studymentioning
confidence: 99%